Performance evaluation of CsI screens for X-ray imaging - 赵博震 秦秀波 冯召东 魏存峰 陈研 王宝义 魏龙 (Chinese physics C, 2014)
CsI film has been one of the most extensively used scintillators for indirect X-ray imaging because of its needle-like micro-structure. The purpose of this paper is to investigate the imaging performance of CsI screen as a function of thickness and radiation quality. Four multilayer scintillation screens with microcolumnar CsI：T1 film （thicknesses of 50 μm, 100 μm, 200μm and 300 μm） included were prepared and coupled to an optical imaging sensor. The modulation transfer function （MTF）, normalized noise power spectrum （NNPS） and detective quantum efficiency （DQE） of these screens were evaluated based on the standard IEC 62220-1, and the results indicated that, in the medium spatial frequency range （1-6 lp/mm）, the MTF of CsI screens with the same thickness was lower when the incident X-ray photon energy was higher, possibly owing to scattering and K-fluorescence re-absorption effects. The NNPS in the higher spatial frequency range （above 8 lp/mm） is dominated by stochastic noise while the entrance surface air Kerma （ESAK） decreases. For 100 μm, 200 μm and 300 μm thick CsI screens, the DQE under RQA7 and RQA9 is lower than that under RQA3 and RQA5 due to low absorption efficiency.